The antimicrobial effect of Bacillus spp filtrates and extracted compound in some pathogenic agent (Journal of the College of Basic Education, 2022)
The study includes isolation and identification of .Bacillus spp samples using different cultural characteristics, physiological and biochemical tests .and VITEK 2 bacterial identification system to confirmed the identification . The results obtained that only 16 isolates of Bacillus spp. were isolated from 50 soil samples which represent 32% in percentage, those isolates were Bacillus subtilis 9 isolates 56.25%, Bacillus firmus 3 isolates 18.75% and Bacillus atrophaeus 4 isolates 25% . examined the antimicrobial activity by using filtrates of 16 Bacillus spp. isolate against tested bacteria included Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Vibrio cholerae, Klebsiella pneumoniae and pathogenic fungal Candida albicans, Candida tropicalis, Aspergillus fumigatus, Cryptococcus neoformance isolates .The results showed that three isolates of Bacillus subtilis B1, B2, B5 showed antimicrobial activity against tested pathogenic bacteria and fungi compare to other Bacillus isolates . The isolate B5 showed higher activity among all the isolates, the higher activity was determined against Staphylococcus aureus and the lowest activity against Salmonella typhi . This isolate B5 had the same activity with fungi when recorded higher inhibition zone diameter against Candida albicans , The effect of the extracted crude Bacillus subtilis isolates B1, B2, B5 by using ethyle acetate showed higher activity than the filtrates . B5 isolate showed highest effects 24mm against G+ve Staphylococcus aureus and 19mm against G-ve E. coli, While the lowest effects was 16mm by isolate B1 on Salmonella typhi, and in fungi B5 isolate had higher activity on Candida albicans 27mm and lowest inhibition zone recorded by B2 isolate was 20mm on Cryptococcus neoformans .